2000
DOI: 10.1042/0264-6021:3500283
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the collagen-like tail of asymmetric acetylcholinesterase with heparin depends on triple-helical conformation, sequence and stability

Abstract: The collagen-like tail of asymmetric acetylcholinesterase (AChE) contains two heparin-binding domains (HBDs) that interact with heparan sulphate proteoglycans, determining the anchoring of the enzyme at the basal lamina and its specific localization at the neuromuscular junction. Both HBDs are characterized by a cluster of basic residues containing a core with the BBXB consensus sequence (where B represents a basic residue and X a non-basic residue). To study the interaction of such HBDs with heparin we have u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…1A). Consistent with this, a decrease in stability was observed when these arginines were replaced by alanines in triple-helical peptides modeling the Torpedo N-terminal HBD (13). Thus, depending on the contacts they establish, arginines could alternatively participate directly in heparin interactions or play a structural role, which in turn can affect the accessibility of the neighboring residues to the ligand.…”
Section: Heparin-binding Capacity Of Colq Resides Exclusively In the mentioning
confidence: 52%
See 4 more Smart Citations
“…1A). Consistent with this, a decrease in stability was observed when these arginines were replaced by alanines in triple-helical peptides modeling the Torpedo N-terminal HBD (13). Thus, depending on the contacts they establish, arginines could alternatively participate directly in heparin interactions or play a structural role, which in turn can affect the accessibility of the neighboring residues to the ligand.…”
Section: Heparin-binding Capacity Of Colq Resides Exclusively In the mentioning
confidence: 52%
“…Triple-helix Structural Properties as Modulators of Heparin Affinity-Previous studies using synthetic peptides have shown a negative correlation between affinity and triple-helical stability (13). Here, ColQ mutants in which a same residue was substituted by alanine or proline, generating an identical array of basic residues but likely to be subjected to different local stability, showed different affinities for heparin.…”
Section: Heparin-binding Capacity Of Colq Resides Exclusively In the mentioning
confidence: 97%
See 3 more Smart Citations